Etched Silicon-on-Insulator Microring Resonator for Ultrasound Measurement - Wenjian Yang; Shijie Song; Keith Powell; Xiaoyi Tian; Liwei Li; Linh Nguyen; Xiaoke Yi (IEEE Photonics Journal)
A novel integrated optical ultrasound sensor based on silicon-on-insulator (SOI) platform is proposed, theoretically analyzed and experimentally demonstrated. By using a selectively etched SOI microring resonator in an add-drop structure, the technique provides a linear and distortion-free sensing response to the ultrasound signal as it prevents the coupling region deformation and removes variations from the power fluctuation of the optical source. The proof-of-concept experimental demonstration of the proposed sensor shows the detection of air-coupled ultrasound pressure at different frequencies and magnitudes, a frequency sensing resolution of 30 Hz and a wide acceptance angle around 75 degrees.